Effect of cellulose nanofibers and plantain peel fibers on mechanical, thermal, physicochemical properties in bio-based composites storage time - Juan Pablo Castañeda-Niño; José Herminsul Mina-Hernández; José Fernando Solanilla-Duque (Results in Engineering)
A completely bio-based composite material was developed from a plantain thermoplastic starch (TPS) reinforced by a 30 % of lignocellulosic fibers from agro-industrial residues of plantain peel, by using a by using the processing sequence based on a twin-screw extrusion process and a hot compression molding to produce the corresponding test specimens. The thermoplastic starch and the bio-based composite material was characterized by tensile test, thermal tests (thermogravimetric analysis and differential scanning calorimetry), and physicochemical tests (contact angle, water absorption, and X-ray diffraction), considering 90 days of storage in controlled conditions. As expected, the reinforcing influence of plantain peel lignocellulosic fibers in the matrix was evidenced during the storage time of 90 days, with better mechanical performance in tensile strenght (5.65 to 1.19 MPa), lower plasticizer migration capacity as indicated by thermogravimetric analysis (TGA), water bsorption (14.2 %) and angle contact (between 48.8 to 58.9 °), presenting greater stability in the crystalline structure than the pure TPS by maintaining the relative crystallinity between 7.7 to 10.44 % and lower thermal stability to 307.4 °C related to the presence of hemicellulose in the peel fibre reinforcement.